Micro-Credentials And The Digital Transformation Of Higher Education - Pappagallo, Sergio (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
Through microcredentials and open badges, education transcends rigid monoliths, evolving into a dynamic mosaic of granular competencies certified. This represents a digital revolution championed by the European Union to foster lifelong learning and employability (Council of the European Union, 2022). This study delves into how these tools, grounded in constructivist principles, democratize education by empowering learners as active architects of knowledge, with badges validating real-world experiences and personalized pathways (Gibson et al., 2015: 403). The objective of this exploratory study is to balance anticipated benefits—such as equity and flexibility—with sociological risks, hypothesizing that, in stratified contexts, micro-credentials may amplify inequalities by reducing human essence to quantifiable skill units (Wheelahan & Moodie, 2021). What is the intrinsic value of microcredentials and open badges? How do they navigate digital and regional divides? Employing documentary analysis of EU policies, Eurostat statistics, and institutional reports (EUA Trends 2024), the article adoptes sociological lens, critiquing neoliberal commodification (Bourdieu, 1986). Future endeavors might incorporate stakeholder interviews and longitudinal studies to map impacts from a qualitative point of view, advancing inclusive policies.